Towards a digital ecology of language learning: An integrative interaction model within the virtual education landscape - Hoerudin, Cecep Wahyu (Edelweiss Applied Science and Technology, 2025)
The rapid advancement of digital technology has transformed the landscape of language learning, demanding a more nuanced understanding of interaction within virtual educational environments. While various studies have explored isolated aspects of digital learning—such as learner engagement, technological tools, and pedagogical strategies—there remains a lack of an integrative model that holistically addresses the complex interplay between these components. This article offers a conceptual synthesis of current literature to construct a comprehensive interaction model grounded in the principles of digital ecology. Drawing on theoretical frameworks from educational psychology, sociocultural theory, and interactionist approaches, the study identifies and organizes key dimensions of interaction—cognitive, affective, and technological—into a unified ecological structure. The proposed model emphasizes the dynamic, reciprocal relationship between learners, content, instructors, and digital environments. Through a structured literature review of studies published in the last decade, the article uncovers both converging trends and critical gaps in existing research. The findings advocate for a shift from fragmented digital pedagogy toward a systems-oriented view that reflects the interconnectedness of the modern language learning experience. This conceptual contribution not only offers a foundation for future empirical investigations but also provides practical implications for instructional design and technology integration in online language education. Ultimately, this paper argues that embracing an ecological perspective is essential for fostering meaningful interaction and sustainable learning outcomes in the digital age.